A (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material and preparation method thereof
By using oxide raw materials and B4C powder, combined with silicon nitride ball milling and in-situ reaction technology, (Ti, Zr, Hf) B2 medium entropy ceramic matrix composite material was prepared, solving the problem of difficult control of grain size and grain boundary strength in the prior art, and achieving high strength, high toughness and good high temperature mechanical properties.
Patent Information
- Application Number
- CN202310337520.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-31
AI Technical Summary
In the prior art, when preparing medium entropy boronide ceramics, it is difficult to effectively control the grain size and grain boundary strength, and impurities are easily introduced during powder mixing, affecting the high-temperature mechanical properties of the material.
The oxide raw material and B4C powder were used as raw materials, and the ball milling and mixing was carried out uniformly by silicon nitride ceramic balls. The reduction reaction was carried out under vacuum and lower temperature conditions. Excess B4C was introduced for in-situ reaction, removing silicon nitride impurities, and forming a fine, uniform second phase of BN and B4C.
The preparation of low-temperature densification, high-strength, high-toughness (Ti, Zr, Hf) B2 medium entropy ceramic matrix composite materials has been achieved. The grains are small and the particle size is uniformly distributed, and the comprehensive mechanical properties of the material such as strength and toughness at high temperatures have been significantly improved.
Smart Images

Figure CN116354730B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-high temperature ceramic material preparation, and in particular to a low-temperature densified high-strength and high-toughness (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite material and a preparation method thereof. Background Art
[0002] In 2004, two research groups, Ye Junwei from National Tsing Hua University in Taiwan and Cantor from Oxford University in the UK, almost simultaneously proposed the concept of high-entropy alloys. They found that melting multiple alloy elements with (nearly) equal atomic ratios at high temperatures easily formed single-phase solid solutions with simple crystal structures such as face-centered cubic, body-centered cubic and hexagonal close-packed structures with random distribution of metal atoms. Since then, the concept of high-entropy alloys has also been extended to the field of high-entropy ceramics, and non-oxide ultra-high temperature ceramic systems such as high-entropy borides, carbides and nitrides have gradually received attention from scientific researchers. High-entropy materials generally exhibit four major effects, namely the high-entropy effect in thermodynamics, the lattice distortion effect in crystallography, the hysteresis diffusion effect in kinetics and the "cocktail" effect in performance. Compared with traditional low-entropy ceramics, entropy-increased ceramics often exhibit good structural stability and functional properties. Diboride ceramics of transition metals of group IVB and VB (M=Ti, Zr, Hf) have excellent comprehensive properties such as high melting point, low saturated vapor pressure, and no solid phase transition, and have important application potential in extreme high temperature service environments such as hypersonic aircraft and rocket propulsion systems. However, there are few reports on the low-temperature densification and high-temperature mechanical properties of medium-entropy boride ceramics at home and abroad.
[0003] Literature (Demirskyi D, Suzuki TS, Yoshimi K, Vasylkiv O.Synthesis of medium-entropy(Zr 1 / 3 Hf 1 / 3 Ta 1 / 3 )B2 using the spark plasma consolidation of diboride powders.Journal of the Ceramic Soiety of Japan.2020;128(11):977-80.) reported that monoboride powders (HfB2, TiB2 and ZrB2) were used as raw materials to prepare (Hf 1 / 3 Ti 1 / 3 Zr 1 / 3 )B2 medium entropy ceramics, the grain size of the obtained dense ceramics is 10-20μm, the room temperature strength of the material is only 310-318MPa, and the fracture toughness is 2.9-3.0MPa·m 1 / 2The above-mentioned medium-entropy ceramics prepared with monovalent boride powder as raw material make it difficult to effectively control the grain size of the material during the sintering process, and the powder will introduce a certain amount of impurities during the mixing process, which is not conducive to the control of the grain size and grain boundary strength of the material, nor is it conducive to improving the high-temperature mechanical properties of the material.
[0004] The literature (Zhang W, Zhang Y, Guo WM, et al. Powder synthesis, density, microstructure and mechanical properties of Hf-based ternary boride ceramics. J Eur Ceram Soc. 2021, 41: 3922-3928.) reported that HfO2, TiO2, ZrO2, B4C and graphite were used as raw materials and (Hf 1 / 3 Ti 1 / 3 Zr 1 / 3 )B2 boride ceramic powder, the method synthesized (Hf 1 / 3 Ti 1 / 3 Zr 1 / 3 )B2 powder contains unreacted HfO2 impurity phase. The presence of oxygen impurity phase is not conducive to the densification of the material. 1 / 3 Ti 1 / 3Zr 1 / 3 )B2 ceramics have a density of 97.2% after sintering at 2000℃, and the sintered ceramics still contain monoclinic HfO2. HfO2 will undergo a phase transition from monoclinic to tetragonal at high temperatures, which is not conducive to improving the high-temperature mechanical properties of the material. Summary of the invention
[0005] In view of the problems in the prior art, the object of the present invention is to provide a low-temperature densified high-strength and high-toughness (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite material and a preparation method thereof.
[0006] According to one aspect of the present invention, a (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material is provided, wherein the composite material has (Ti, Zr, Hf)B2 as a main phase and BN and B4C as secondary phases.
[0007] Preferably: the chemical composition of the (Ti, Zr, Hf) B2 is (Ti x Zr y Hf z )B2, where 0.2≤x≤0.40, 0.2≤y≤0.40, x+y+z=1.0.
[0008] According to another aspect of the present invention, a method for preparing the above-mentioned (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material is provided, comprising the following steps:
[0009] Step 1, preparing a ceramic composite powder, wherein the ceramic composite powder has (Ti, Zr, Hf) B2 as a main phase and BN and B4C as secondary phases, wherein the mass fraction of BN is (1.6-3.2) wt%, and the mass fraction of B4C is (2-4) wt%;
[0010] Step 2: Sinter the ceramic composite powder under pressure to obtain a (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material.
[0011] Preferably: Step 1 comprises:
[0012] Step 1.1, mixing oxide raw materials TiO2 powder, ZrO2 powder, HfO2 powder and B4C powder according to the raw material molar ratio of TiO2:ZrO2:HfO2:B4C=x:y:z:u; wherein 0.2≤x≤0.40, 0.2≤y≤0.40, x+y+z=1.0, 0.89≤u≤0.96;
[0013] Step 1.2, the powder after mixing is mixed, dried and sieved using ethanol or acetone as a dispersant and silicon nitride ceramic balls as a ball milling medium;
[0014] Step 1.3, heating the mixed powder to 1200-1400° C. under vacuum conditions, keeping the temperature for 0.5-4 hours, and then heating to 1500-1650° C. and keeping the temperature for 0.5-4 hours to obtain a ceramic composite powder.
[0015] Preferably, the mass loss of the silicon nitride grinding balls in step 1.2 accounts for 1.8-3.5wt% of the mixed powder.
[0016] Preferably, in step 1.2, a planetary ball mill or a roller jar mill is used for mixing, and the rotation rate is 50-600 r / min.
[0017] Preferably: in step 2, the material is heated to 1650°C under vacuum or high-purity argon protection, kept warm for 0.5h, and then an axial pressure of 30-120MPa is applied, followed by heating to 1700-1900°C and sintering for 0.1-4h to obtain a (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material.
[0018] Preferably, the oxygen content of the (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material obtained in step 2 is not more than 0.7wt%.
[0019] Preferably, the relative density of the (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material obtained in step 2 is not less than 97.5%.
[0020] Preferably, the bending strength and fracture toughness of the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material prepared in step 2 at 1600°C are 450-850 MPa and 4.0-7.0 MPa·m 1 / 2 .
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] (1) The technical solution has a simple process, the synthesized composite powder and the prepared ceramic have low oxidation content, small grains and uniform particle size distribution;
[0023] (2) This technical solution uses a one-time mixing method. On the one hand, it utilizes an in-situ reaction to effectively remove the impurity phase of the ball milling medium introduced during the ball milling mixing process. On the other hand, while introducing the second phase, it also avoids the introduction of ball milling impurities and oxygen impurities in the secondary mixing. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Other features, objectives and advantages of the present invention will become more apparent from a reading of the detailed description of non-limiting embodiments made with reference to the following accompanying drawings.
[0025] Figure 1 This is the XRD spectrum of the (Ti, Zr, Hf) B2-based powder synthesized in Example 1, wherein the ordinate is Intensity and the abscissa is 2Theta (θ).
[0026] Figure 2 This is the SEM morphology of the fracture surface of the (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material in Example 1 and the energy spectrum point scanning result diagram.
[0027] Figure 3 This is the energy spectrum point scanning result diagram of the BN phase in the (Ti, Zr, Hf)B2 medium entropy ceramic-based composite material in Example 1.
[0028] Figure 4 This is the energy spectrum point scanning result diagram of the B4C phase in the (Ti, Zr, Hf)B2 medium entropy ceramic-based composite material in Example 1. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.
[0030] Since B4C has high hardness and high wear resistance, in the preparation process of (Ti, Zr, Hf) B2 ceramics, in the mixture using B4C powder as raw material, the impurities of ball milling medium will inevitably be introduced. The ball milling medium is introduced into the ceramic by grinding and wearing of B4C powder, which will have an adverse effect on the purity and high temperature mechanical properties of the material.
[0031] The embodiment of the present invention uses oxide powder (TiO2 powder, ZrO2 powder, HfO2 powder) and B4C powder as raw materials, uses silicon nitride ceramic balls for ball milling and uniform mixing, and prepares (Ti, Zr, Hf) B2 powder with fine particle size and low oxygen content through reduction reaction under vacuum and low temperature conditions. At the same time, by introducing an excessive amount of B4C, a part of B4C is used to react in situ with the silicon nitride introduced by ball milling, which can not only remove silicon nitride impurities, but also react to generate a BN second phase with fine grains and uniform dispersion. The other part of B4C exists in the form of a residual second phase. The BN and residual B4C phases generated by the in-situ reaction are beneficial to inhibiting the growth of the material during the sintering process and promoting the densification of the material. At the same time, B4C is beneficial to improving the high-temperature interface strength of the material, and BN is beneficial to improving the fracture toughness of the material. The introduction of B4C and BN second phases can be beneficial to improving the comprehensive mechanical properties of the material such as strength and toughness at high temperatures.
[0032] In an embodiment of the present invention, a (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material is provided, wherein the composite material has (Ti, Zr, Hf) B2 as the main phase and BN and B4C as the secondary phases. This not only utilizes silicon nitride impurities, but also facilitates densification and comprehensive mechanical properties.
[0033] The preferred chemical composition of (Ti, Zr, Hf) B2 is (Ti x Zr y Hf z )B2, where 0.2≤x≤0.40, 0.2≤y≤0.40, x+y+z=1.0.
[0034] Preferably, the content of BN in the composite material is (1.6-3.2) wt%, the content of B4C is (2-4) wt%, and the balance is the main phase. The oxygen content is not more than 0.7 wt%.
[0035] It is further preferred that the relative density of the (Ti, Zr, Hf)B2-based medium entropy ceramic material is not less than 97.5%, and the open porosity is not higher than 1.0%.
[0036] The average grain size of the main phase (Ti, Zr, Hf) B2 is 0.5-8.0 μm, more preferably 0.5-5.0 μm. The secondary phase BN is a lamellar morphology, distributed at the grain boundaries and triple boundaries of (Ti, Zr, Hf) B2, with an average grain size of 0.1-1.5 μm; B4C is a spherical morphology, with an average grain size of 0.3-3 μm.
[0037] The ceramic-based composite material preferably has a bending strength and a fracture toughness of 450 to 850 MPa and 4.0 to 7.0 MPa·m at 1600°C, respectively. 1 / 2 .
[0038] At the same time, in an embodiment of the present invention, a method for preparing a (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite material is provided, wherein oxide raw materials (TiO2 powder, ZrO2 powder, HfO2 powder) and B4C powder are uniformly mixed by ball milling using silicon nitride ceramic ball media, and heated to 1200-1650°C in two steps under vacuum conditions, and the synthesized powder is a composite powder. The powder has (Ti, Zr, Hf) B2 as the main phase and BN and B4C as the secondary phases. The (Ti, Zr, Hf) B2-based medium-entropy ceramic composite powder is then pressure-sintered to obtain a high-strength and high-toughness (Ti, Zr, Hf) B2-based composite medium-entropy ceramic material.
[0039] Preferably, the following steps are included in sequence:
[0040] Step 1, the oxide raw materials TiO2 powder (purity ≥ 99.5%, 0.01-0.5 μm), ZrO2 powder (purity ≥ 99.5%, 0.05-0.5 μm), HfO2 powder (purity ≥ 99.5%, 0.05-0.5 μm) and B4C powder (purity ≥ 99.5%, 0.1-2.0 μm) are prepared according to the raw material molar ratio of TiO2: ZrO2: HfO2: B4C = x: y: z: u; wherein 0.2≤x≤0.40, 0.2≤y≤0.40, x+y+z=1.0, 0.89≤u≤0.96;
[0041] Step 2, mixing, drying and sieving the powder prepared in step 1 using ethanol or acetone as a dispersant and silicon nitride ceramic balls as ball milling media; wherein the mass ratio of the balls to the materials is preferably 2:1 to 4:1.
[0042] Preferably, a planetary ball mill or a roller jar mill is used for mixing, with a rotation rate of 50 to 600 r / min. The mass loss of silicon nitride grinding balls during ball milling mixing accounts for 1.8 to 3.5 wt% of the mixed powder; further preferably, a roller jar mill is used for mixing, with a rotation rate of 50 to 300 r / min.
[0043] Step 3, heating the mixed powder of step 2 to 1200-1400° C. under vacuum conditions, keeping the temperature for 0.5 to 4 hours, and then heating to 1500 to 1650° C. and keeping the temperature for 0.5 to 4 hours;
[0044] Preferably, the oxygen content of the ceramic powder is not more than 0.7wt%, the mass fraction of BN is (1.6-3.2)wt%, the mass fraction of B4C in the powder is (2-4)wt%, and the remainder is the main phase.
[0045] Step 4, grinding and sieving the (Ti, Zr, Hf) B2-based medium-entropy ceramic composite powder prepared in step 3, heating to 1650°C under vacuum or high-purity argon protection, keeping warm for 0.5h and applying axial pressure, then heating to 1700-1900°C and sintering for 0.1-4h to obtain high-strength and high-toughness (Ti, Zr, Hf) B2-based medium-entropy ceramics.
[0046] The preferred axial pressure is 30-120 MPa and the pressurization rate is 3-12 MPa / min.
[0047] The present invention is described below with specific embodiments:
[0048] Example 1
[0049] The oxide raw materials TiO2 powder (purity ≥99.5%, 0.01-0.5μm), ZrO2 powder (purity ≥99.5%, 0.05-0.5μm), HfO2 powder (purity ≥99.5%, 0.05-0.5μm) and B4C powder (purity ≥99.5%, 0.1-2.0μm) are mixed according to the raw material molar ratio of TiO2:ZrO2:HfO2:B4C=x:y:z:u; wherein x=0.333, y=0.333, z=0.334, u=0.89.
[0050] Ethanol was used as solvent, silicon nitride ceramic balls were used as grinding media, the ball-to-material mass ratio was 2:1, and the materials were mixed on a mixer at a rate of 150 r / min. The ball milling time was set according to the wear of the silicon nitride balls so that the silicon nitride content introduced was about 1.8 wt%. The ethanol solvent in the slurry was evaporated and removed at 55° C. using a rotary evaporator, and then dried at 70° C. in a blast drying oven, and then sieved.
[0051] The raw material mixed powder was heated to 1300°C at a rate of 10°C / min under vacuum conditions for 2.5h, and then heated to 1650°C at a rate of 10°C / min and kept at that temperature for 0.5h. The XRD spectrum of the synthesized powder is as follows: Figure 1 As shown, the powder is mainly composed of (Ti, Zr, Hf) B2, the oxygen content of the powder is 0.49wt%, and no oxide impurity phase is found by XRD.
[0052] The synthesized (Ti, Zr, Hf) B2-based ceramic composite powder was ground and sieved in a mortar, loaded into a graphite mold, and heated to 1650°C at a rate of 10°C / min under vacuum conditions and kept warm for 0.5h. Then, flowing argon was introduced, and the pressure was increased to 30MPa at a rate of 3MPa / min. The temperature was increased to 1800°C at a rate of 10°C / min, and sintered for 1h. The temperature was then reduced to 1700°C at a rate of 15°C / min, and the pressure was unloaded and cooled with the furnace.
[0053] The fracture surface of the prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material is shown in Figure 2. Figure 2 As shown, the lamellar phase is BN, and its energy spectrum results are as follows Figure 3 As shown, it also contains B4C phase, and its energy spectrum results are as follows Figure 4 shown.
[0054] The material composition is about 96.4wt% (Ti, Zr, Hf) B2-1.6wt% BN-2wt% B4C. Since the content of BN and B4C is relatively small, the XRD spectrum does not detect these two phases. The density is 98.5%, the open porosity is 0.3%, and the oxygen content is 0.55wt%.
[0055] The SEM morphology of the ceramic fracture surface is as follows Figure 3 As shown, the average grain size is 2.5μm. After high temperature mechanical properties testing, the bending strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composite materials at 1600℃ are 651MPa and 6.5MPa·m 1 / 2 .
[0056] Example 2
[0057] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that the powders were sintered at 60 MPa for 1 h.
[0058] The density of the prepared (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite material reaches 98.9%, the open porosity is 0.2%, and the average grain size is 2.0 μm.
[0059] After high temperature mechanical properties testing, the bending strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composite materials at 1600°C were 733MPa and 6.8MPa·m 1 / 2 .
[0060] Example 3
[0061] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that the powders were sintered at 120 MPa for 0.5 h.
[0062] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a density of 98.9%, an open porosity of 0.2%, and an average grain size of 1.0 μm.
[0063] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 763 MPa and 7.0 MPa·m 1 / 2 .
[0064] Example 4
[0065] The ingredients were mixed, the powder was prepared and sintered according to the method of Example 1, except that the powder was sintered at 1900° C. for 1 hour.
[0066] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a density of 98.9%, an open porosity of 0.2%, and an average grain size of 3.5 μm.
[0067] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 680 MPa and 4.8 MPa·m 1 / 2 .
[0068] Example 5
[0069] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that the pressure applied to the powders was 60 MPa and the sintering was performed at 1900° C. for 1 h.
[0070] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a density of 99.2%, an open porosity of 0.1%, and an average grain size of 2.5 μm.
[0071] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600℃ are 697MPa and 5.8MPa·m 1 / 2 .
[0072] Example 6
[0073] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that the pressure applied to the powders was 120 MPa and the sintering was performed at 1900° C. for 0.1 h.
[0074] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a density of 99.5%, an open porosity of 0.1%, and an average grain size of 0.9 μm.
[0075] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 779 MPa and 4.0 MPa·m 1 / 2 .
[0076] Example 7
[0077] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that the pressure applied to the powders was 120 MPa and the sintering was performed at 1700° C. for 1.0 h.
[0078] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a density of 97.9%, an open porosity of 0.2%, and an average grain size of 0.5 μm.
[0079] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 700 MPa and 7.0 MPa·m 1 / 2 .
[0080] Example 8
[0081] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.2, y=0.4, z=0.4 and u=0.89. The prepared (Ti, Zr, Hf) B2 medium entropy ceramic composite material had a composition of about 96.4wt% (Ti, Zr, Hf) B2-1.6wt% BN-2wt% B4C.
[0082] The material density is 97.5%, the open porosity is 0.4%, and the average grain size is 3.0μm.
[0083] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 450 MPa and 5.2 MPa·m 1 / 2 .
[0084] Example 9
[0085] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.2, y=0.4, z=0.4, u=0.89, and the pressure applied by the powder was 60 MPa.
[0086] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0087] The material density is 98.5%, the open porosity is 0.3%, and the average grain size is 2.8μm.
[0088] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 489 MPa and 6.0 MPa·m 1 / 2 .
[0089] Example 10
[0090] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.2, y=0.4, z=0.4, u=0.89, the pressure applied to the powder was 120 MPa, and the sintering time was 0.5 h.
[0091] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0092] The material density is 99.2%, the open porosity is 0.1%, and the average grain size is 1.3μm.
[0093] The four-point bending strength and fracture toughness of (Ti, Zr, Hf) B2-based medium-entropy ceramics at 1600℃ are 583MPa and 6.2MPa·m 1 / 2 .
[0094] Embodiment 11
[0095] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.4, y=0.4, z=0.2, u=0.89, the pressure applied to the powder was 60 MPa, and the sintering temperature was 1700°C.
[0096] The components of the prepared (Ti, Zr, Hf) B2-based medium-entropy ceramic composite material are 96.1wt% (Ti, Zr, Hf) B2-1.9wt% BN-2wt% B4C.
[0097] The material density is 98.0%, the open porosity is 0.3%, and the average grain size is 0.7μm.
[0098] The four-point bending strength and fracture toughness of (Ti, Zr, Hf) B2-based medium-entropy ceramics at 1600℃ are 634MPa and 6.8MPa·m 1 / 2 .
[0099] Example 12
[0100] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.4, y=0.4, z=0.2, u=0.89, the pressure applied to the powder was 60 MPa, and the sintering temperature was 1800°C.
[0101] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.1wt% (Ti, Zr, Hf)B2-1.9wt% BN-2wt% B4C.
[0102] The material density is 98.5%, the open porosity is 0.2%, and the average grain size is 0.9μm.
[0103] The four-point bending strength and fracture toughness of (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite phase at 1600℃ are 674MPa and 6.5MPa·m 1 / 2 .
[0104] Embodiment 13
[0105] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.4, y=0.4, z=0.2, u=0.89, the pressure applied to the powder was 120 MPa, and the sintering temperature was 1900°C for 0.1 h.
[0106] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.1wt% (Ti, Zr, Hf)B2-1.9wt% BN-2wt% B4C.
[0107] The material density is 97.9%, the open porosity is 0.3%, and the average grain size is 0.7μm.
[0108] The four-point bending strength and fracture toughness of (Ti, Zr, Hf) B2 medium-entropy ceramic-based composites at 1600℃ are 739MPa and 4.8MPa·m 1 / 2 .
[0109] Embodiment 14
[0110] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1, except that x=0.4, y=0.4, z=0.2, u=0.96, the content of silicon nitride introduced by ball milling was 3.5wt%, and the pressure applied to the powder was 60MPa.
[0111] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 92.8wt% (Ti, Zr, Hf)B2-3.2wt% BN-4wt% B4C.
[0112] The material density is 99.5%, the open porosity is 0.1%, and the average grain size is 1.5μm.
[0113] The four-point bending strength and fracture toughness of (Ti, Zr, Hf) B2 medium-entropy ceramic-based composites at 1600°C are 700 MPa and 6.0 MPa·m 1 / 2 .
[0114] Embodiment 15
[0115] The ingredients were mixed, the powder was prepared and sintered according to the method of Example 1, except that the multiphase powder was heated at 1200° C. for 0.5 h and at 1500° C. for 4 h.
[0116] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0117] The material density is 99.1%, the open porosity is 0.1%, and the average grain size is 2.0 μm.
[0118] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 610 MPa and 6.3 MPa·m 1 / 2 .
[0119] Example 16
[0120] The ingredients were mixed, the powder was prepared and sintered according to the method of Example 1, except that the composite powder was heated at 1200° C. for 4 h and at 1650° C. for 0.5 h.
[0121] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0122] The material density is 98.7%, the open porosity is 0.2%, and the average grain size is 1.5μm.
[0123] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600℃ are 695MPa and 5.8MPa·m 1 / 2 .
[0124] Embodiment 17
[0125] The ingredients were mixed, the powder was prepared and sintered according to the method of Example 1, except that the multiphase powder was heated at 1400° C. for 2 h and at 1500° C. for 2 h when preparing the multiphase powder.
[0126] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0127] The material density is 99.2%, the open porosity is 0.1%, and the average grain size is 0.8μm.
[0128] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600℃ are 756MPa and 6.0MPa·m 1 / 2 .
[0129] Comparative Example 1
[0130] The ingredients were mixed, powders were prepared and sintered according to the method of Example 1. The difference from Example 1 is that two-step solid-phase heating was not used when preparing the composite powder, but sintering was performed directly at 1650° C. for 3 h.
[0131] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 96.4wt% (Ti, Zr, Hf)B2-1.6wt% BN-2wt% B4C.
[0132] The density of the material is 97.0%, the open porosity is 1.2%, and the average grain size is 10.0 μm.
[0133] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 400 MPa and 2.5 MPa·m 1 / 2 .
[0134] Comparative Example 2
[0135] The ingredients are mixed, the powder is prepared and sintered according to the method of Example 1, except that silicon nitride is not used but ZrO2 balls are used for mixing.
[0136] The prepared (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material has a composition of approximately 97wt% (Ti, Zr, Hf)B2-3wt% B4C.
[0137] The material density is 96.5%, the open porosity is 2.8%, and the average grain size is 12μm.
[0138] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 350 MPa and 2.5 MPa·m 1 / 2 .
[0139] Comparative Example 3
[0140] The ingredients are mixed, the powder is prepared and sintered according to the method of Example 1, except that x=0.1, y=0.45, z=0.45 and u=0.89.
[0141] The prepared (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material has a composition of approximately 96.4 wt% (Ti, Zr, Hf) B 2- 1.6wt%BN-2wt%B4C.
[0142] The material density is 95.5%, the open porosity is 3.2%, and the average grain size is 9μm.
[0143] The flexural strength and fracture toughness of (Ti, Zr, Hf) B2 medium entropy ceramic-based composites at 1600°C are 300 MPa and 3.0 MPa·m 1 / 2 .
[0144] It can be seen from the above examples that when the preparation method, silicon nitride balls and proportions of the technical solution of the present invention are not adopted, the prepared medium-entropy ceramic-based composite material has a low density, a high porosity, a large grain size, and poor comprehensive mechanical properties. The technical solution of the present invention has a simple process, the synthesis of composite powders and the prepared ceramics have low oxidation, small grains, and uniform particle size distribution. The prepared medium-entropy ceramic-based composite material has excellent mechanical properties such as strength and toughness at high temperatures.
[0145] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing a (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material, characterized in that: The following steps are involved: Step 1.1, mixing oxide raw materials TiO2 powder, ZrO2 powder, HfO2 powder and B4C powder according to the raw material molar ratio of TiO2:ZrO2:HfO2:B4C=x:y:z:u; wherein 0.2≤x≤0.40, 0.2≤y≤0.40, x+y+z=1.0, 0.89≤u≤0.96; Step 1.2, the powder after mixing is mixed, dried and sieved using ethanol or acetone as a dispersant and silicon nitride ceramic balls as a ball milling medium; Step 1.3, heating the mixed powder to 1200-1400° C. under vacuum conditions, keeping the temperature for 0.5-4 hours, and then heating to 1500-1650° C. and keeping the temperature for 0.5-4 hours to obtain a ceramic composite powder.
2. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 1, characterized in that: The ceramic composite powder has (Ti, Zr, Hf) B2 as a main phase and BN and B4C as secondary phases, wherein the mass fraction of BN is (1.6-3.2) wt%, and the mass fraction of B4C is (2-4) wt%. The steps further include: Step 2: Sinter the ceramic composite powder under pressure to obtain a (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material.
3. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 1, characterized in that: The mass loss of the silicon nitride grinding balls in step 1.2 accounts for 1.8-3.5wt% of the mixed powder.
4. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 1, characterized in that: In the step 1.2, a planetary ball mill or a roller jar mill is used for mixing, and the rotation speed is 50 to 600 r / min.
5. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 2, characterized in that: In the step 2, the material is heated to 1650° C. under vacuum or high-purity argon protection, kept warm for 0.5 h, and then an axial pressure of 30 to 120 MPa is applied. The material is then heated to 1700 to 1900° C. and sintered for 0.1 to 4 h to obtain a (Ti, Zr, Hf) B2 medium-entropy ceramic-based composite material.
6. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 5, characterized in that: The oxygen content of the (Ti, Zr, Hf)B2 medium-entropy ceramic-based composite material obtained in step 2 is not more than 0.7wt%.
7. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 5, characterized in that: The relative density of the (Ti, Zr, Hf)B2 medium entropy ceramic-based composite material obtained in step 2 is not less than 97.5%.
8. The method for preparing the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material according to claim 5, characterized in that: The bending strength and fracture toughness of the (Ti, Zr, Hf) B2 medium entropy ceramic-based composite material prepared in step 2 at 1600° C. are 450-850 MPa and 4.0-7.0 MPa·m 1 / 2 .
Citation Information
Patent Citations
Metal diboride base sintered ceramic and method of producing same
US5019540A